Negative Selection Assay Based on Stimulation of T Cell Receptor Transgenic Thymocytes with Peptide-MHC Tetramers - Rybakin, Vasily (Public Library of Science, 2012)
Thymocyte negative selection is a requirement for the development of self tolerance. Although it is possible to assay the induction of cell death in thymocytes in vitro using antibody cross-linking, this stimulus is much stronger than the normal range of T cell receptor ligands that could be encountered during normal development. Signaling in thymocytes is finely balanced between positive and negative selection stimuli, where a negative selecting ligand can be only marginally higher affinity than a positive selecting ligand. We have therefore developed an assay for the induction of negative selection that can distinguish such cases, and that is amenable to high-throughput analysis. The assay is based on the induction of activated caspase 3 in thymocytes expressing a defined T cell receptor, after stimulation with MHC-peptide tetramers in vitro for 24 hours or less.